PENGARUH KEAHLIAN SELLER TERHADAP SUPPLY CHAIN RELATIONSHIP DAN DAMPAKNYA TERHADAP KEPUASAN PELANGGAN (STUDI PADA USAHA MEUBEL DI KOTA BANDA ACEH) - Ramadhan, Wirdah Irawati (Departemen Manajemen, 2017)
The purpose of study is to find out (1) the effect of seller expertise on customer satisfaction, (2) the effect of expertise seller to supply chain relationship, (3) the effect of supply chain relationship to customer satisfaction, (4) the effect of seller expertise on customer satisfaction through the supply chain relationship as a mediating variable. This study was conducted on small and medium industrial enterprises (IKM) in the Banda Aceh city. The object of study related to testing influences and supply chain expertise seller relationship to customer satisfaction. The number of respondents in this study were 50 furniture business in Banda Aceh taken by convenience sampling. Equipment data analysis used in this study is a multilevel regression (hierarchical linier methods) which is operated by software Statistics Package for Social Science (SPSS) 21th version. Results of study expertise seller effect on customer satisfaction, expertise seller affect the supply chain relationship in the small and medium enterprises in the city of Banda Aceh, and supply chain relationships influence on customer satisfaction in the small and medium enterprises in the city of Banda Aceh and the results of this study also revealed that seller expertise effect on customer satisfaction through the supply chain relationship as a mediating variable.Keyword: Expertise Seller, Supply Chain Relationship and Customer Satisfaction